1983
DOI: 10.1677/joe.0.0980165
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ovarian hormones on regulation of energy balance in Zucker rats

Abstract: Congenitally obese Zucker rats showed greater food intake, less running in activity wheels and greater body weight and fat content than the normal phenotype. Their food intake, running and body weight did not change significantly with the phase of the oestrous cycle. Ovariectomy had no effect on these variables or on body composition. Oestradiol replacement had little effect. Zucker rats of normal weight, however, showed a normal pattern of responses to the oestrous cycle, ovariectomy and oestradiol administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The ultimate body weight appears to be independent of ovarian status. Additionally, Shaw et al (1983) reported that ovariectomy appears to have no effect on rate of weight gain. In the current study, ovariectomy at 21 days increased the rate of body weight gain from birth to peak weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate body weight appears to be independent of ovarian status. Additionally, Shaw et al (1983) reported that ovariectomy appears to have no effect on rate of weight gain. In the current study, ovariectomy at 21 days increased the rate of body weight gain from birth to peak weight.…”
Section: Discussionmentioning
confidence: 99%
“…The CBA/J strain of mice used in the current study is a special strain that looses its ovarian follicles by 1 year of age (Parkening et al, 1984) making direct comparisons with mice of other strains or rats difficult. Differences in results may be related to experimental design, as Shaw et al (1983) utilized congenitally obese Zucker rats. Clark and Tarttelin (1982) utilized Sprague-Dawley rats of the Simonsen strain and final data collection extended to only 15 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of oestradiol to increase activity is counteracted by progesterone (122). Activity, food intake, and body weight also vary with the oestrous cycle, with activity peaking at times when circulating oestradiol levels are highest and food intake and body weight are lowest (123, 124). Interpretation is made more difficult because locomotion is most often measured using running wheels, which have effects on activity and energy expenditure independent of energy balance.…”
Section: Sensorsmentioning
confidence: 99%
“…The ability of oestradiol to increase activity is counteracted by progesterone (122). Activity, food intake, and body weight also vary with the oestrous cycle, with activity peaking at times when circulating oestradiol levels are highest and food intake and body weight are lowest (123,124).…”
Section: Sensorsmentioning
confidence: 99%
“…Many of the characteristics of the obese female Zucker rat are similar to those of ovariectomized rats, thus suggesting subnormal estrogen status. These characteristics include hyperphagia, obesity and above-normal lean body mass (Radcliffe and Webster 1976, 1979, Shaw et al 1983. Also, obese female Zucker rats exhibit decreased ovarian and uterine weights, functional sterility, delayed vaginal opening and ovarian cycle irregularities compared to lean female Zucker rats (Saiduddin et al 1973, Bray et al 1976).…”
Section: Evidence For Subnormal Estrogen Status Of Female Zucker Ratsmentioning
confidence: 99%